Improved FastICA algorithm for data optimization processing in intrusion detection - Ye DU; dan ZHANGYa; hong LIMei; wei ZHANGDa (Tongxin xuebao)
For the purpose of achieving the better data optimizat sing results in intrusion detection, an improved FastICA algorithm was proposed. The weighted correlation coefficient was adopted in the phase of albinism processing to reduce information loss, and the Newton's iterative method was improved for third-order convergence. The algorithm was introduced concretely, meanwhile the time complexity was analyzed in detail. The experiment shows that the method has the advantages of less times of iteration and fast speed of convergence, which can effectively decrease the losses of data and increase the efficiency of data optimization in in ion detection.